FUZZY LOGIC SIMULATIONS FOR A SMART AIR CONDITIONING SYSTEM - Dr. I. Valliammal; Dr.K.Mathevan Pillai; Dr. T. Manimozhi; Dr.K. Raja (Utilitas Mathematica, 2025)
The temperature control, fan speed, and other features of the air conditioning system we use every day are all manually automated. Recent air conditioners offer automatic temperature control, variable fan speed, variable compressor speed, and more. However, using a Fully Logic Control System, we have refined it in this study to move automation one step further ahead. We count the number of people in the room using an IR sensor, and the temperature and fan speed are then adjusted accordingly. We estimate the room's size using sonar, and based on this data, we determine the fin's tilt position and maintain fan speed. We determine the inside temperature using an external temperature and humidity sensor. These are the three variables or ways by which we calculate the temperature, fan speed, and fin direction necessary to maintain the desired temperature.